Strain Effects on the Diffusion Properties of Near-Surface Self-Interstitial Atoms and Adatoms in Tungsten - Sun, Bochuan; Maroudas, Dimitrios; Wirth, Brian D.; Martínez, Enrique (Frontiers in Materials, 2021)
Tungsten (W) is a candidate for the plasma-facing components and divertor in future fusion applications. The material will be subject to a large particle influx (mainly helium and hydrogenic species) that will form bubbles. As bubbles grow, they compress the material, adding to thermal stresses, and eject self-interstitial atoms (SIAs - isolated or in clusters) to release internal pressure. These SIAs diffuse towards the surface in large stress/strain fields and on the surface are thought to act as precursors for nanotendril formation (also known as fuzz) that develops on the material surface modifying its morphology. In this work we analyze the effect of strain on the diffusion properties of both SIAs and adatoms. Relying on atomistic simulations, we compute the average time that a SIA created in the center of a tungsten slab takes to reach a {110} surface for different strains and temperatures. This time relates to the SIA diffusivity and allows to compute the activation energy and dipole tensor including surface effects. We observe a large strain effect that significantly modifies the propensity for SIAs to reach the surface and, hence, to cluster to form dislocation loops in bulk. Strain also alters the diffusivity of the adatom although to a lesser extent. Finally, we report on the resulting surface roughness evolution and its dependence on strain.